ROLE OF CAROTID DOPPLER IN CORONARY ARTERY DISEASE - Khan, Shamrez; Ahmed, Syed Afzal; Nuri, M.M.H; Khalid, Muhammad; Rashid, Azhar; Rashid, Azhar; Mehmood, Azhar (Pakistan Armed Forces Medical Journal, 2006)
Objective: To find out the Intima media thickness (IMT) of carotid artery disease in coronary artery disease and to identify hemodynamically significant stenosis (i.e.>70%) in patients undergoing coronary artery bypass surgery. Design: A descriptive study. Place & Duration of Study: The study was conduct at AFIC & MH Rawalpindi from 2003 to 2004. Patients and Methods: One hundred patients of triple, double and single vessel coronary artery disease were studied. There were 85 male and 15 female patients, ranging from 35 to 77 years. The patients were studied by Toshiba Ultrasound Machine equipped with high frequency linear transducers. In 10 patients having more that 70 % ICA stenosis, conventional angiography was done. Results: Intima-media thickness of common carotid artery was increased in 92 patients with mean value of 1.1 mm. Plaques were seen in 92 patients with commonest location at carotid bifurcation with extension into the origin of ICA. 15 patients has >70%, 10 patients > 50 % stenosis and 67 patients in the range of 1-50 % stenosis. 6 patients showed normal intima-media thickness with no evidence of plaque. In two patients ultrasound could not locate bifurcation of CCA. Doppler ultrasound showed 98 % sensitivity in diagnosis of > 70 % stenosis. Conclusion: Doppler ultrasound is a non-invasive imaging modality of choice in evaluation of extra-cranial carotid artery disease.